2013
DOI: 10.1542/peds.2012-1928
|View full text |Cite
|
Sign up to set email alerts
|

Waning Immunity to Pertussis Following 5 Doses of DTaP

Abstract: OBJECTIVE: To assess the risk of pertussis by time since vaccination in children in Minnesota and Oregon who received 5 doses of acellular pertussis vaccines (DTaP). METHODS: These cohort analyses included Minnesota and Oregon children born between 1998 and 2003 who had 5 DTaP doses recorded in state Immunization Information Systems. Immunization records and statewide pertussis surveillance data were combined. Incidence rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
124
1
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(141 citation statements)
references
References 24 publications
11
124
1
5
Order By: Relevance
“…Although some first-generation acellular vaccines had poor immunity and efficacy, double-blinded clinical trials and field-efficacy studies for the US-licensed acellular vaccines estimated the short-term efficacy to be excellent: ∼85% after three doses and 98% after five doses (28)(29)(30). However, recent cohort and case-control studies concluded that 5 y following the fifth aP dose, children are fourfold to 15-fold more likely to acquire pertussis compared with within the first year, consistent with waning aP immunity (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Although some first-generation acellular vaccines had poor immunity and efficacy, double-blinded clinical trials and field-efficacy studies for the US-licensed acellular vaccines estimated the short-term efficacy to be excellent: ∼85% after three doses and 98% after five doses (28)(29)(30). However, recent cohort and case-control studies concluded that 5 y following the fifth aP dose, children are fourfold to 15-fold more likely to acquire pertussis compared with within the first year, consistent with waning aP immunity (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the 1997 recommendations, the DTaP vaccine series was to be administered in five separate doses at the following ages: 2 months, 4 months, 6 months, between 15 and 18 months of age, and between 4 and 6 years old (40,41). Therefore, it is reasonable to assume that any child born in 1998 or later in the United States that was immunized for pertussis would have received the acellular vaccine (11,12).…”
Section: Discussionmentioning
confidence: 99%
“…The age group 5 years and younger was selected because children age 5 years and younger had the highest incidence rate of pertussis in 2012 (8). The age group 10 to 14 years was selected because it was assumed that children born between 1998 and 2000 only received the acellular vaccine (11,12). Analysis of the 10 to 14 years age group helps to understand the impact of waning immunity on the 2012 pertussis outbreak (9)(10)(11)(12).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of explanations for pertussis resurgence have been proposed, ranging from improvements in surveillance and diagnostics (7) to reduced protection afforded by vaccination, whether due to the waning of vaccine-derived immunity (8), the evolution of the etiological agent (the bacterium Bordetella pertussis) (9), the switch from whole-cell to acellular vaccines (10), or the invasion and spread of Bordetella congeners (11). It has also been demonstrated that even in the absence of changes in the nature of transmission, vaccine, or reporting, pertussis resurgence might be expected in some countries as an inevitable consequence of insufficient historical vaccination (12).…”
mentioning
confidence: 99%